2014
DOI: 10.14419/ijamr.v4i1.3799
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of Adomain decomposition method and the new integral transform “Elzaki transform’’

Abstract: In this article, we present a comparative study between Adomain decomposition method and the new integral transform "Elzaki Transform". We use the methods to solve the linear Partial differential equations with constant coefficients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Through examples, it has been shown that the approximate solutions acquired by trapezoidal rule are in good agreement with exact solutions obtained through transformation method. [4] conducted comparative study between Adomian Decomposition Method (ADM) and Elzaki transform. Both methods have been used to solve linear partial differential equations with constant coefficients.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Through examples, it has been shown that the approximate solutions acquired by trapezoidal rule are in good agreement with exact solutions obtained through transformation method. [4] conducted comparative study between Adomian Decomposition Method (ADM) and Elzaki transform. Both methods have been used to solve linear partial differential equations with constant coefficients.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lately, to solve the linear system, Tarig M. Elzaki and Salih M. Elzaki produced a new integral transformation, it was Elzaki transform [23], which then used by Tarig [24] to solve common differential equations with more details. For the same purpose, Adam [25] conducted a comparative investigation between two methods, i.e. Adomain Decomposition and Elzaki Transform, and reported that both techniques were powerful and efficient.…”
Section: Introductionmentioning
confidence: 99%